An altemative peptide sequencing procedure for low budget laboratories - Yagüe, Jesús; Bubis, José (Ciencia)
We standardized the amino-terminal sequencing of peptides by using manual Edman chemistry followed by the separation of the derivatives obtained by high-performance liquid chromatography (HPLC). Initially, the 3-phenyl-2-thiohydantoins (PTH) of the twenty common amino acids were chemically synthesized and purified individually. With the exception of PTHMet and PTH-Val, which coeluted when various gradient conditions were used, we were able to separate the remaining eighteen PTH-amino acids by reversed-phase HPLC on a C18 column. The pair PTH-Met/PTH-Val eluted from the column as a single peak at a different retention time than the other PTH derivatives. Then, the primary structure of a synthetic heptapeptide, kemptide, was verified using the standard Edman degradation procedure followed by HPLC separation of the PTH-amino acid liberated in each cycle. The sequence obtained, Leu-Arg-Arg-Ala- Ser-Leu-Gly, corresponds to the expected published sequence. Thus, the methodology reported here represents a simple. sensitive, reproducible, and inexpensive procedure that provides an alternative to peptide sequencing by automatic sequenators or mass spectrometers.